Human Robot Interaction for Teaching Generalisation of a Task - Sena, Aran; Howard, Matthew; Zhao, Yuchen (King's College London, 2018)
This is a dataset collected from 30 participants in a study on human-robot interaction during programming by demonstration. It was conducted under KCL ethics approval LRS-16/17-3800. This data is accompanying data to a paper that was accepted to the IEEE International Conference on Robotics and Automation (ICRA) 2018.
Keywords: Human; Robot; Interaction; Programming; by; Demonstration; Visualisation; Generalisation.